Optimal Values and Selection Criteria for Resistors Used in Neutral Grounding - Taslimov, Abduraxim; Raximov, Feruz; Rakhimov, Farrukh (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: this article presents a systematic approach to selecting and optimizing resistances for neutral grounding in 20 kV electrical networks. The main focus is on enhancing electrical safety, reducing the risk of overvoltage, and ensuring the effectiveness of relay protection systems. The study addresses key aspects such as determining optimal resistance values, aligning with transformer grounding voltage requirements, and adhering to relevant safety standards. The article offers practical recommendations for engineers and designers by integrating technical and economic perspectives, and includes real-world examples and research on the topic. Aim: this article discusses the determination and implementation of optimal resistance parameters for neutral grounding in 20 kV electrical networks, with the aim of enhancing electrical safety, reducing the risk of overvoltage, and ensuring the effectiveness of relay protection systems. This approach is intended to improve the stability of the electrical network, ensure the continuity of technological processes, and reduce costs. Methods: the research was conducted using a systematic approach, including systematic analysis of energy audit results for electrical networks, regression analysis, and theoretical planning methods. For selecting and optimizing resistances for neutral grounding in 20 kV electrical networks, mathematical models were used to describe time-dependent functions of electromechanical parameters, and regression analysis was employed to find optimal solutions. Results: the research results specifically pertain to determining the optimal parameters for transformers and resistors for neutral grounding in the 20 kV electrical network of the Regional Branch of the Joint-Stock Company "Regional Electric Networks" in Navoi. The tests were conducted using MATLAB/Simulink, and the results facilitated the development of effective solutions for overvoltage, short circuits, system stability, and electrical network safety.